A novel optimized silver nitrate staining method for visualizing the osteocyte lacuno-canalicular system - Jinlian Wu; Jinlian Wu; Chunchun Xue; Qiang Li; Hongjin Wu; Jie Zhang; Chenglong Wang; Weiwei Dai; Libo Wang (Frontiers in Endocrinology)
A 50% (w/v, equivalent to 2.943 mol/L) silver nitrate solution is commonly used to stain and characterize the osteocyte lacuno-canalicular system (LCS) in bone biology research. However, variability in reagent concentrations and types, along with inconsistent staining procedures, have limited the broader application of this method in osteocyte research. In this study, we present a novel optimized silver nitrate staining technique aimed at addressing these limitations. This new method utilizes a 1 mol/L (equivalent to 16.987%, w/v) silver nitrate solution in combination with a type-B gelatin-formic acid solution at various concentrations (0.05%-0.5% gelatin and 0.05%-5% formic acid, or 1%-2% gelatin and 0.1%-2% formic acid) in volume ratios of 4:1, 2:1, or 1:1, or a 0.5 mol/L silver nitrate solution at a 4:1 ratio. The staining process is carried out for 1 hour under ultraviolet light or 90 minutes under regular room light (or dark), followed by washing with Milli-Q water to terminate the reaction. We applied this new method to stain the osteocyte LCS in bone samples from different species and pathological bone models. The technique consistently produced clear, distinct staining patterns across all samples. Moreover, our novel method revealed a greater number of LCS compared to the traditional 50% silver nitrate solution. This suggests that the commonly used 50% silver nitrate method may disrupt or inadequately reveal the LCS in bones, potentially leading to an underestimation of LCS density and number. In conclusion, our novel silver nitrate staining method provides a simpler and more cost-effective alternative to the traditional technique. By offering a more accurate and comprehensive analysis of the LCS across species, this approach has the potential to advance research on osteocyte morphogenesis, as well as the functional and evolutionary adaptations of the osteocyte LCS across different taxa.